2013
DOI: 10.32398/cjhp.v11i1.1519
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physical Activity Participation between University Employees With and Without a Worksite Health Promotion Program

Abstract: The purpose of this study was to assess differences in physical activity (PA) among university employees with and without a formal health promotion program. Three state university campuses without health promotion programs and four campuses with a program participated in this study. PA participation was assessed via survey to all campus employees. PA was compared for those with (n=426) and without a program (n=371). The results indicated that there was no significant difference (p>.05) in the amount of vigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…Strenuous and light days of PA were not statistically significant, but both trended towards increasing, with moderate days of PA increasing significantly. These results are consistent with previous research that indicated the effectiveness of WHP programs in increasing PA among university employees [7,18,19,20]. Additional research indicates that employees with WHP programs tend to be more active [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Strenuous and light days of PA were not statistically significant, but both trended towards increasing, with moderate days of PA increasing significantly. These results are consistent with previous research that indicated the effectiveness of WHP programs in increasing PA among university employees [7,18,19,20]. Additional research indicates that employees with WHP programs tend to be more active [20].…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with previous research that indicated the effectiveness of WHP programs in increasing PA among university employees [7,18,19,20]. Additional research indicates that employees with WHP programs tend to be more active [20]. This is important, as research supports that increased PA provides significant health benefits to the individual [21].…”
Section: Discussionsupporting
confidence: 90%
“…Workplace health promotion programs (WHPPs) have existed for decades, with many documented benefits to both employees and organizations [1][2][3][4][5]. Despite the company and employee benefits, organizations often struggle to incorporate long-term, cost-effective programming into their structure due to budget, staffing, and/or time constraints [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[17] A wide variety of worksite interventions range from traditional exercise classes, [14] walking or step programs, [18] use of pedometers, [19] and cosmetic and structural enhancements to encourage physical activity including behavior and counseling techniques. [14] Depending on the program in place, some of these worksite health promotion programs have been shown to improve healthy behavior, [20,21,22,23,24] while other studies do not show a change in improvement [25,26,27] or had high attrition rates. [26,27,28] Recently, researchers demonstrated that a 12-week faculty and staff exercise program (exercising three times per week) resulted in significant improvements in measures of muscular endurance, flexibility, and balance.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Depending on the program in place, some of these worksite health promotion programs have been shown to improve healthy behavior, [20,21,22,23,24] while other studies do not show a change in improvement [25,26,27] or had high attrition rates. [26,27,28] Recently, researchers demonstrated that a 12-week faculty and staff exercise program (exercising three times per week) resulted in significant improvements in measures of muscular endurance, flexibility, and balance. [23] Even minimal physical activity interventions using a 12-week walking program at a worksite has shown to reduce body mass index (BMI), blood glucose, and total cholesterol.…”
Section: Introductionmentioning
confidence: 99%